Instrumentalizem oblikovanja edukacijskih politik - Barle Lakota, Andreja (Šolsko polje, 2007)
Some things seem so obvious that they are taken as read. The sphere of education is often one of these things. It appears that even in expert discussions these spheres are losing their social and historical dimension, their integration. Perhaps it is this that impedes us, so that we constantly talk about the same thing, in the same way, and always seek solutions in the sphere of the known. Perhaps the difficulty lies in the fact that there is no clear distance between the shaping of visions and utopias and their transference into practice. Or perhaps the problem is that instrumentalism, even in the sphere of education policy design, has paralysed the recognition and transcending of the existing.
Keywords: edukacija; trajnostni razvoj; vzgoja in izobraževanje; znanje